A social-ecological system approach to Bali cattle raising in Timor Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Firman A, Nono OH. 2021. A social-ecological system approach to Bali cattle raising in Timor Island, Indonesia. Biodiversitas 22: 3585-3593. Cattle raising in East Nusa Tenggara play important role in the daily life of local people including to fulfill nutritional needs, to generate cash income, to develop social relationships, and to maintain religious activities. On the island of Timor, the type of cattle mostly kept by farmers is Bali cattle. This type of cattle perfectly suits the environmental and social conditions of the island. The purpose of this study was to investigate the interaction of social-ecological systems (SESs) and other systems that were able to maintain the sustainability of Bali cattle raising in Timor Island.  All components in the system that interact with each other were studied through in-depth interviews with informants (15 cattle farmers, five community leaders, five cattle traders, and 10 staff of livestock services district and province levels). The results showed that the SESs approach could provide an explanation on the relationship between resource systems, resource units, governance systems, and users as well as systems that are outside SESs, namely the market and government policies, which altogether were able to improve Bali cattle raising sustainability. Farmers had an important role in Bali cattle raising and their habitat environment. Local and export markets played a role in providing value for Bali cattle raising. The local government maintained the balance of supply and demand for Bali cattle through the East Nusa Tenggara Governor Regulations No. 78 of 2019. Therefore, the research has succeeded in identification of feed resources in savanna and steppe and provide an opportunity to increase the cattle population on the island of Timor. The interaction between farmers and their environment has been well established, however, it is necessary to improve the quality of forage feed in grazing land.
Keywords: Bali cattle, social ecology systems, breeding, conservation